2016
DOI: 10.3389/fendo.2016.00102
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Skeletal Integrity and Marrow Adiposity during High-Fat Diet and after Weight Loss

Abstract: The prevalence of obesity has continued to rise over the past three decades leading to significant increases in obesity-related medical care costs from metabolic and non-metabolic sequelae. It is now clear that expansion of body fat leads to an increase in inflammation with systemic effects on metabolism. In mouse models of diet-induced obesity, there is also an expansion of bone marrow adipocytes. However, the persistence of these changes after weight loss has not been well described. The objective of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
100
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(127 citation statements)
references
References 64 publications
17
100
0
3
Order By: Relevance
“…In our study, we examined dietary effects during growth—from weaning to adulthood (18 to 26 weeks on diet). Within this time frame, both positive and negative effects of high‐fat diet on cortical bone have been reported in male C57BL/6J mice. The main difference between these two prior studies was the use of 45% high‐fat diet with diacylglycerol enrichment in the former versus 60% lard/soybean oil in the latter .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our study, we examined dietary effects during growth—from weaning to adulthood (18 to 26 weeks on diet). Within this time frame, both positive and negative effects of high‐fat diet on cortical bone have been reported in male C57BL/6J mice. The main difference between these two prior studies was the use of 45% high‐fat diet with diacylglycerol enrichment in the former versus 60% lard/soybean oil in the latter .…”
Section: Discussionmentioning
confidence: 96%
“…Within this time frame, both positive and negative effects of high‐fat diet on cortical bone have been reported in male C57BL/6J mice. The main difference between these two prior studies was the use of 45% high‐fat diet with diacylglycerol enrichment in the former versus 60% lard/soybean oil in the latter . The dietary composition we used (42% milk fat) was comparable to the first study and, like that report, we demonstrated positive absolute effects of high‐fat diet on cortical bone.…”
Section: Discussionmentioning
confidence: 96%
“…Ultimately, the physiologic underpinnings of weight loss in an obese person are likely to be distinct from those of weight loss in a normal or underweight person (as in anorexia). This distinction is suggested by the results of a recent study in mice, in which mice fed a high‐fat diet then switched to a normal diet experienced weight loss and a decrease in marrow fat at the tibia and femur …”
Section: Discussionmentioning
confidence: 99%
“…For example, mice with high fat diet-induced obesity show much higher osmium staining of proximal tibial marrow lipid than lean mice. Elevated lipid in proximal tibia is due to an increase in both BMA number and size 35, 37, 38 (Figure 2). In contrast, neither bone marrow lipid nor the size/number of BMAs is different in distal tibial cBMAT of lean and obese mice (Figure 2).…”
Section: Development and Regulation Of Bmat In Humans And Rodentsmentioning
confidence: 99%